Enhancing Adolescent Physical Fitness and Well-Being: A School-Based High-Intensity Interval Training Program - Petar Mitić; Rade Jovanović; Nikola Stojanović; Valentin Barišić; Nebojša Trajković (Journal of Functional Morphology and Kinesiology)
Background: The aim of this study is to investigate the effects of a school-based high-intensity interval training (HIIT) program on quality of life and physical fitness in adolescents. Methods: The study included 60 male adolescents (16.2 ± 0.6 years), randomly assigned to one of two groups: the HIIT group (n = 30) and the control group (CG, n = 30). Participants completed the KIDSCREEN-27 questionnaire to evaluate quality of life and physical fitness tests, including vertical jump, repetitive strength, agility, and flexibility. The experimental program consisted of a 12-week intervention integrated into the warm-up phase of regular physical education (PE) classes. Each PE class lasted 45 min, with the HIIT regimen occupying 10 min of the warm-up phase. The HIIT sessions followed a Tabata-style structure, performed twice weekly. A two-way ANOVA with repeated measures assessed group and time interaction effects. Results: The results revealed changes in physical well-being following the HIIT intervention (p = 0.01) compared to the control group (p = 0.42). The results of the two-way ANOVA with repeated measures revealed interaction effects between group and time for the various fitness tests, countermovement jump (p = 0.04), 4 × 10 m agility test (p = 0.02), medicine ball throw test (p = 0.04), and sit-ups (30 s) (p = 0.01). Conclusions: This study highlights the effectiveness of school-based HIIT in significantly enhancing physical well-being and physical fitness among adolescents.